Methodology and applications of elemental mapping by laser induced breakdown spectroscopy - Limbeck, A; Brunnbauer, L; Lohninger, H; Pořízka, P; Modlitbová, P; Kaiser, J; Janovszky, P; Kéri, A; Galbács, G (Analytica chimica acta, 2021)
In the last few years, LIBS has become an established technique for the assessment of elemental concentrations in various sample types. However, for many applications knowledge about the overall elemental composition is not sufficient. In addition, detailed information about the elemental distribution within a heterogeneous sample is needed. LIBS has become of great interest in elemental imaging studies, since this technique allows to associate the obtained elemental composition information with the spatial coordinates of the investigated sample. The possibility of simultaneous multi-elemental analysis of major, minor, and trace constituents in almost all types of solid materials with no or negligible sample preparation combined with a high speed of analysis are benefits which make LIBS especially attractive when compared to other elemental imaging techniques. The first part of this review is aimed at providing information about the instrumental requirements necessary for successful LIBS imaging measurements and points out and discusses state-of-the-art LIBS instrumentation and upcoming developments. The second part is dedicated to data processing and evaluation of LIBS imaging data. This chapter is focused on different approaches of multivariate data evaluation and chemometrics which can be used e.g. for classification but also for the quantification of obtained LIBS imaging data. In the final part, current literature of different LIBS imaging applications ranging from bioimaging, geoscientific and cultural heritage studies to the field of materials science is summarized and reviewed.
Keywords: Data processing; Elemental imaging; Laser induced breakdown spectroscopy; Application examples; Technical requirements